2012
DOI: 10.1186/bcr3160
|View full text |Cite
|
Sign up to set email alerts
|

Variants in the vitamin D pathway, serum levels of vitamin D, and estrogen receptor negative breast cancer among African-American women: a case-control study

Abstract: Introduction: Gene amplification of CCND1 is observed in a subgroup of breast cancers with poor prognosis, whereas overexpression of the protein cyclin D 1 has been linked to both worse and better clinical outcome. CCND1 amplification and protein overexpression have also been associated with resistance to treatment with tamoxifen or even to a potentially detrimental effect of tamoxifen. Methods: To clarify these challenging and partly contrasting treatment predictive and prognostic links for cyclin D 1 we anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
51
1
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 32 publications
(46 reference statements)
8
51
1
3
Order By: Relevance
“…2013; Shahbazi et al, 2013) but not in others (Buyru et al, 2003;Hefler et al, 2004;VandeVord et al, 2006;Trabert et al, 2007;Sinotte et al, 2008;Gapska et al, 2009;McKay et al, 2009;Anderson et al, 2011;Rollison et al, 2012;Mishra et al, 2013); Apa1 was found with positive relationship in some breast cancer studies (Curran et al, 1999;Sillanpaa et al, 2004;Dalessandri et al, 2012), but negative in others (Cui et al, 2001;Hou et al, 2002;Chakraborty et al, 2009;Anderson et al, 2011;Engel et al, 2012;Mishra et al, 2013); the same as Taq1, with associations in some studies (Cui et al, 2001;, but not in others (Curran et al, 1999;Dunning et al, 1999;Lundin et al, 1999;Hou et al, 2002;Newcomb et al, 2002;Buyru et al, 2003;Sillanpaa et al, 2004;John et al, 2007;Abbas et al, 2008;Chakraborty et al, 2009;Gapska et al, 2009;Anderson et al, 2011;Engel et al, 2012;Mishra et al, 2013); Cdx2, positive in some studies (Anderson et al, 2011;Yao et al, 2012; but not in others (Abbas et al, 2008;Zhou et ...…”
mentioning
confidence: 82%
“…2013; Shahbazi et al, 2013) but not in others (Buyru et al, 2003;Hefler et al, 2004;VandeVord et al, 2006;Trabert et al, 2007;Sinotte et al, 2008;Gapska et al, 2009;McKay et al, 2009;Anderson et al, 2011;Rollison et al, 2012;Mishra et al, 2013); Apa1 was found with positive relationship in some breast cancer studies (Curran et al, 1999;Sillanpaa et al, 2004;Dalessandri et al, 2012), but negative in others (Cui et al, 2001;Hou et al, 2002;Chakraborty et al, 2009;Anderson et al, 2011;Engel et al, 2012;Mishra et al, 2013); the same as Taq1, with associations in some studies (Cui et al, 2001;, but not in others (Curran et al, 1999;Dunning et al, 1999;Lundin et al, 1999;Hou et al, 2002;Newcomb et al, 2002;Buyru et al, 2003;Sillanpaa et al, 2004;John et al, 2007;Abbas et al, 2008;Chakraborty et al, 2009;Gapska et al, 2009;Anderson et al, 2011;Engel et al, 2012;Mishra et al, 2013); Cdx2, positive in some studies (Anderson et al, 2011;Yao et al, 2012; but not in others (Abbas et al, 2008;Zhou et ...…”
mentioning
confidence: 82%
“…Details of the study design, inclusion criteria, and collection of survey data and biospecimens have been previously described (26,27). Briefly, incident breast cancer cases were identified in four boroughs of the metropolitan New York City using hospital-based case ascertainment, and in seven counties in New Jersey (NJ) using population-based case ascertainment through the NJ State Cancer Registry, a participant of the National Cancer Institute's Surveillance, Epidemiology, and End Results (SEER) program.…”
Section: Study Populationmentioning
confidence: 99%
“…Estudios de laboratorio, preclínicos y clínicos, sugieren que variantes genéticas en las vías metabólicas de la vitamina D están relacionadas con una mayor prevalencia de cáncer de mama, sostienen que los niveles bajos de 1,25-OH-D3 se pueden comportar como factor de riesgo para dicho cáncer ya que en todas las células del tejido glandular mamario se expresan receptores de vitamina D que podrían estar relacionados con procesos de división celular 37,40 . Se ha comprobado que los niveles altos de vitamina D inhiben la proliferación de células cancerígenas e induce la apoptosis en roedores, pero en los humanos estos mecanismos no se han esclarecido en su totalidad 40 .…”
Section: Patologías Asociadas a Los Bajos Niveles De Vitamina Dunclassified
“…Se ha comprobado que los niveles altos de vitamina D inhiben la proliferación de células cancerígenas e induce la apoptosis en roedores, pero en los humanos estos mecanismos no se han esclarecido en su totalidad 40 .…”
Section: Patologías Asociadas a Los Bajos Niveles De Vitamina Dunclassified